Bugaboo: A Spanish case of circulation and co-production of video games. - Meda-Calvet, Ignasi; Wade, Alex (Cogent Arts & Humanities, 2016)
Melanie Swalwell has discussed how 'locality has largely been left out of game history, at least until recently'. Moreover, much of the research and literature about the still young history of video games has been conducted following a cult of celebrity mostly concerned with highlighting American and Japanese perspectives. Swalwell, discusses 'the great historic diversity of contexts and games to play with', and considering that technological innovation is a multi-centred complex process-- not the linear progression depicted in many writings--this article focuses on the specific context of the early eighties in Spain, in a decisive moment wherein personal computers began to reach markets, even though information on how to program them was confusing and difficult to access. While both, programming and gameplay are sometimes described as solitary or antisocial activities, this paper explores the landscape of Spanish computer games in the early eighties through a case study of the Spanish computer game “Bugaboo (The Flea)” programmed by Francisco Portalo and Francisco Suárez, ironically, released before in the UK (in 1983) rather than Spain. By following the traces that this game was leaving behind (even before it was programmed), I will show the performative potential that this game had, first of all, as a way of tinkering and learning among enthusiasts and practitioners onto how to master micro computers and, afterwards, becoming a digital commodity as well as a bargaining chip in the negotiations to distribute Amstrad micro computers in Spain.